Extramural Venous Invasion as Prognostic Factor of Recurrence in Stage 1 and 2 Colon Cancer - E. E. van Eeghen; M. J. Flens; M. M. R. Mulder; R. J. L. F. Loffeld (Gastroenterology Research and Practice)
Aim. Extramural venous invasion (EMVI) is a prognostic indicator in patients with colorectal cancer. However, its additional value in patients with stage 1 and 2 colorectal cancer is uncertain. In the present study, the incidence of EMVI and the hazard ratio for recurrence in patients with stage 1 and 2 colon cancer were studied. Methods. 184 patients treated for stage 1 and 2 colon cancer were included with a follow-up of at least 5 years. Chart review was performed and EMVI was assessed by two separate pathologists. EMVI was scored with additional caldesmon staining on the resection specimen. Primary outcomes were recurrence-free survival (RFS) measured through the Cox regression analysis and prevalence of EMVI. Results. There were 10 cases of EMVI and 3 cases of intramural venous invasion (IMVI) all occurring in patients with stage 2 disease corresponding to a prevalence of 9%. Thirty-one percent of the patients with venous invasion experienced recurrence versus 14% in patients without, corresponding with a hazard ratio of 2.39 (p=0.11). Conclusion. The present study demonstrates a trend towards an increased risk of recurrence in patients with stage 2 colon cancer with venous invasion. This warrants consideration of adjuvant chemotherapy despite the lack of lymph node metastases.